Theory and Simulation of Incipient Instability in Gas-Solid Fluidization - Look, Kar Yang (2006)
The mechanism of incipient instability in gas-solid fluidized bed was investigated by using Computational Fluid Dynamics (CFD) simulation – FLUENT version 6.1.18. The Finite Volume Method (FVM) is employed to simulate the complex flow behaviours and heterogeneous structure of the gas-solid fluidized bed. Fluidization of Geldart group A, B and C particles were simulated.